Role of combined oral contraceptive pills as add back therapy in patients receiving GNRH analogue. - Kalaivani G, Shuhaila A, Rizal AM, Norzilawati MN (Department of Surgery, UKM Medical Centre, 2014)
This was a randomised control trial involving 25 patients on GnRH analogue in a university hospital over period of six months. The patients were randomised into two groups, twelve patients were treated with GnRH analogue and low dose COCP (treatment group) as add back therapy and thirteen patients were treated with GnRH analogue alone (control group) for three months.